Perceptions About Brand Image and Promotion on Consumer Purchase Decisions in the Indonesian Home Education Parenting Program at Pt Naruna Karya Bersama - Noviansyah, Kafita Yogi; Dewanti, Mentari Clara (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to determine perceptions regarding "Brand Image and Promotion on Consumer Purchasing Decisions in the Indonesian Parenting Home Education Program at PT Naruna Karya Bersama". The research method uses qualitative methods with data collection techniques used in this research, namely observation and interviews. The results of this research explain that the perception of brand image and promotion on consumer purchasing decisions in the Home Education Indonesia parenting program is very positive. This is based on interviews conducted with consumers, namely with school principals, teachers and parents who explained that this parenting activity really helped increase their knowledge and made them aware of how to care for children properly and correctly.